(3eYJbOGJ Phj bOQGJ GdMSGH GdYbdj GdeNJdaI fMh OQGSI GdQjGVjGJ (B:s (3OQGSI MGdI Ydj GdJdGejP hGdeYde hGdhGdOjf (B/s - (3,YdG eMeO YHO GdebUhO YHO GdMdjes; (3hGFd YHO Gddg eMeO Ydis; (3QMGH eMeO Wgs (2024)
(3gOa GdHMK GdMGVQ mGdj GdJYQa Ydj eYJbOGJ GdJdGejP Phj bOQGJ GdMSGH GdYbdj GdeNJdaI fMh OQGSI GdQjGVjGJ, hGdJYQa Ydj eYJbOGJ GdeYde hGdhGdOjf fMh mGSJNOGe GdMSGH GdYbdj, hMSe GdJYGQV Hjf GdOQGSGJ GdJj JfGhdJ eYJbOGJ GdJdGejP hGdeYdejf hGdhGdOjf fMh GdMSGH GdYbdj hOQGSI GdQjGVjGJ, hbO TedJ YjfI GdHMK (B(15) (3JdejPB,(B(8) (3eYdejf, (B(7) (3hGdOjf, hJQGhMJ CYeGQ GdJdGejP ef(B(11-12) (3SfhGJ, ef JdGejP GdUa GdChd GdmGYOGOj OGQSj GdMSGH GdYbdj, heYdej GdJdGejP hcPdc ChdjGA CehQge GdJGHYjf dCcGOjejI GdWad GdYHbQj ddJfejI, hmGYJeO GdHMK Ydj GdJMdjd Gdcjaj; dCfg GdCfSH deTcdI GdHMK, hmGTJed GdHMK Ydj eLehYI ef GdBOhGJ hgj(B: (3mGNJHGQ GdMSGH GdYbdj ddJdGejP(B((3mGYOGO GdHGMKI(B) (3ebjGS eYJbOGJ fMh OQGSI GdQjGVjGJ ddJdGejP(B((3mGYOGO GdHGMKI(B)(3, mGSJeGQI ebGHdI TNUjI ddJYQa HUhQI CcKQ YebB Ydj GdeYJbOGJ fMh OQGSI GdQjGVjGJ ddJdejP(B((3mGYOGO GdHGMKI(B)(3, ebjGS eYJbOGJ fMh GdMSGH GdYbdj dcdB ef GdYde hGdhGdOjf(B((3mGYOGO GdHGMKI(B)(3, mGSJeGQI ebGHdI TNUjI ddeYJbOGJ fMh GdMSGH GdYbdj dcdB ef GdeYde hGdhGdOjf(B((3mGYOGO GdHGMKI(B)(3, hCSaQJ fJGFL GdHMK Ydj CgejI OQGSI GdMSGH GdYbdj ddJdGejP, hLhO aQb aj GdbOQGJ GdYbdjI GdMSGHjI Hjf ef jOQShf GdMSGH GdYbdj hHjf ef jcJahf HGdefgL GdeOQSj ddQjGVjGJ dUGdM GdJdGejP GdPjf jOQShf GdMSGH GdYbdj(B.s
The main aim of the current research is to explore the beliefs of students with different mathematical abilities towards the study of mathematics, as well as to understand the beliefs of teachers and parents regarding the use of mathematical abilities. The study also aims to reconcile the conflicts between studies that have addressed the beliefs of students, teachers, and parents towards mathematical abilities and the study of mathematics. The research sample included 15 students, 8 teachers, and 7 parents. The ages of the students ranged from 11 to 12 years, from the first grade of middle school, studying mental arithmetic affiliated to the Genius Child Academy for Development. The research relied on qualitative analysis as it suits the research problem. The research utilized a set of instruments, including a mental arithmetic test for students, a scale of beliefs towards the study of mathematics for students, a personal interview questionnaire to gain a deeper understanding of beliefs towards the study of mathematics for students, a scale of beliefs towards mathematical abilities for teachers and parents, and a personal interview questionnaire for beliefs towards mathematical abilities for both teachers and parents. The research results emphasized the significances of studying mental arithmetic for students and revealed differences in arithmetic abilities between those who study mental arithmetic and those who rely solely on the school curriculum in mathematics, in favor of students studying mental arithmetic.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B223-247.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdQjGVjGJs -- (3WQb GdJOQjSs; (3GdeYJbOGJ GdeYQajIs -- (3GdMSGH GdYbdjs -- (3GdQjGVjGJs